2011
DOI: 10.1364/ol.36.003873
|View full text |Cite
|
Sign up to set email alerts
|

Lasing in thulium-doped polarizing photonic crystal fiber

Abstract: We describe lasing of a thulium-doped polarizing photonic crystal fiber. A 4 m long fiber with 50 μm diameter core, 250 μm diameter cladding, and d/Λ ratio of 0.18 was pumped with a 793 nm diode and produced a polarized output with a polarization extinction ratio (PER) of 15 dB and an M(2) of <1.15. An intracavity polarizer and half-wave plate minimally increased the PER to 16 dB. The output power had 35% slope efficiency relative to the absorbed pump power. The maximum cw output power was limited to 4 W due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Using an ASE seed, no spectral modulations were observed with amplification, and using a laser seed an M 2 < 1.07 confirms nearly single transverse mode propagation. The combiner's gain efficiency is not optimal at 22.1 %, however it is believed that optimizing the fabrication of the pump combiner and/or the passive to active fiber splice, the performance can reach levels seen in [4,6,7] for free-space pumped Tm:PCF lasers. This novel component is highly attractive for an all-fiber CPA system, with capabilities of reaching > 100 kW peak power in the fiber.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an ASE seed, no spectral modulations were observed with amplification, and using a laser seed an M 2 < 1.07 confirms nearly single transverse mode propagation. The combiner's gain efficiency is not optimal at 22.1 %, however it is believed that optimizing the fabrication of the pump combiner and/or the passive to active fiber splice, the performance can reach levels seen in [4,6,7] for free-space pumped Tm:PCF lasers. This novel component is highly attractive for an all-fiber CPA system, with capabilities of reaching > 100 kW peak power in the fiber.…”
Section: Discussionmentioning
confidence: 99%
“…Free-space amplification in Tm:PCF has shown higher slope efficiencies [4,6,7], however these configurations used counter-propagating pump coupling. These reduced slope efficiencies could be due to: defects in the Tm:PCF, poor pump coupling, poor signal coupling, or negative contributions from co-propagating pump scheme and/or sub-optimal fiber length.…”
Section: Slope Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…-doped fibers have recently attracted much interest due to their potential application in material processing, laser sensing, free-space optical communication, and bio-medical (Modsching et al 2011;Creeden et al 2014;Tang et al 2010;Zhang et al 2005a;Liu et al 2013;He et al 2013). Lots of studies have been demonstrated to obtain high power fiber laser (Goodno et al 2009;Schellhorn et al 2009; http://www.laserfocusworld.com/articles/ print/volume-48/issue-08/features/holmium-doped-silica-fiber-designs-extend-fiber-lasersbeyond-2-um.html) or pumped light source for generating the longer laser wavelength with Ho 3?…”
Section: Introductionmentioning
confidence: 99%
“…3,4 One of the key factors of this rapid technological advance has been the exploitation of innovative Double-Cladding Photonic Crystal Fibers (DC-PCFs) designs, allowing a significant enlargement of the mode effective area while maintaining Single Mode (SM) propagation, thereby raising the threshold for the onset of nonlinearities while ensuring high output beam quality. [5][6][7] In principle, the same PCF design approaches used for Yb-doped fibers can be applied to realize Tm-doped fibers, 8,9 with the advantage that operation at longer wavelengths allows SM propagation with larger effective area. Nevertheless, Tm-doped PCF technology is still young, and the development of fibers with very large mode field diameter to be used for the amplification of high-energy pulses is still at an early research stage.…”
Section: Introductionmentioning
confidence: 99%